O papel da Assembleia Legislativa do Estado do Maranhão na formulação das políticas públicas de educação - Efraim Lopes Soares (2022)
This thesis deals with the role of the Assembleia Legislativa do estado do Maranhão (Legislative Assembly of the State of Maranhão) in the formulation of public education policies, taking into account the connections among institutional arrangements, the relationship between the state Executive and Legislative Powers and the content of educational policies in legislatures comprised in the period from 2003 to 2018. The study starts from two clues discussed in the literature, which are essential in the construction of the chapters presented: 1) the formation of the Brazilian Federative State, as well as the distribution of competences between Union and States and between Governors and Deputies, (ALMEIDA, 2000; FERREIRA FILHO, 1990; MORAES, 2003; 2009; GONZALEZ, 2011; TOMIO; RICCI, 2012b; CURY, 2010; 2011; RANIERI, 2020); and, 2) the rules that define the relations between the Executive and Legislative Powers (FIGUEIREDO; LIMONGI, 1995; 1998; 2001; SANTOS, 2001; 2003; 2006; ABRANCHES, 1988; PEREIRA; MULLER, 2000; BORGES, 2018). This is a case study, operationalized through content and statistical analysis, this study has a quantitative-qualitative nature, whose methodological proposal involved bibliographic and documental research. Empirical evidence points to a strong state Executive Power and that, regardless of the party scenario that prevails within ALEMA, always obtains legislative success and insists that the legislation on education created by parliamentarians does not depart from its interests. It is an “imperial Executive”, due to the great accumulation of powers concentrated in the figure of the Governor. The interpretation that is made, regarding the contrast observed between the quantity and quality of the propositions that integrate the ALEMA education agenda, is that the result is not only related to the strength of the Executive, but, above all, to the institutional weaknesses of the Legislative Power. These weaknesses are expressed by the failure to approve their projects, the inability to override vetoes, the difficulty of forming majorities in the face of the particularism of the initiatives, added to the decision-making centrality around the Board of Directors and the Constitution and Justice Commission, as well as the lack of technical capacity of its proposers. Having proven its political dependence in the face of legislative impossibilities, what seems evident is ALEMA's weakness through the deficit found in the production of educational policies, denouncing, above all, that the deputies fail to guarantee, as constitutional legislators, the right to education in the State of Maranhão.